2011
DOI: 10.1021/am200693x
|View full text |Cite
|
Sign up to set email alerts
|

Non-lift-off Block Copolymer Lithography of 25 nm Magnetic Nanodot Arrays

Abstract: Although nanolithographic techniques based on self-assembled block copolymer templates offer tremendous potential for fabrication of large-area nanostructure arrays, significant difficulties arise with both the lift-off and etch processes typically used for pattern transfer. These become progressively more important in the limit of extreme feature sizes. The few techniques that have been developed to avoid these issues are quite complex. Here, we demonstrate successful execution of a nanolithographic process b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 45 publications
(89 reference statements)
1
69
0
Order By: Relevance
“…[9][10][11][12][13] For example, porous alumina templates have been used to fabricate PMA antidot arrays with engineered coercivity at the expense of a very rough topography. [14][15][16] Thin films of self-organized di-block copolymers provide an alternative route to fabricate nanostructured templates for metal films, [9][10][11]13,[17][18][19] that have been used to control different magnetic properties such as bit size in patterned magnetic media, 9 exchange bias in Fe/FeF 2 bilayers 17 or coercivity in permalloy films, 18 and spin valves. 19 Most of the works on local modifications of PMA have been focused on Co(Pt,Pd) and Fe(Pt,Pd) alloys [3][4][5]7,10,12 due to their strong PMA and large Q factors (Q ¼ K N /2pM S 2 with K N the perpendicular anisotropy and M S the saturation magnetization).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] For example, porous alumina templates have been used to fabricate PMA antidot arrays with engineered coercivity at the expense of a very rough topography. [14][15][16] Thin films of self-organized di-block copolymers provide an alternative route to fabricate nanostructured templates for metal films, [9][10][11]13,[17][18][19] that have been used to control different magnetic properties such as bit size in patterned magnetic media, 9 exchange bias in Fe/FeF 2 bilayers 17 or coercivity in permalloy films, 18 and spin valves. 19 Most of the works on local modifications of PMA have been focused on Co(Pt,Pd) and Fe(Pt,Pd) alloys [3][4][5]7,10,12 due to their strong PMA and large Q factors (Q ¼ K N /2pM S 2 with K N the perpendicular anisotropy and M S the saturation magnetization).…”
Section: Introductionmentioning
confidence: 99%
“…After successfully reducing pore diameter from 30 nm to 14 nm ( Figure 8 g and h), permalloy was evaporated on the ZnO "nanocrucibles" followed by a "Damascene-type" process reported earlier [ 90 ] to leave well-ordered ZnO nanocrucibles surrounding the permalloy dots (Figure 8i-m). The material showed ferromagnetic multidomain/vortex state at larger diameters but at reduced diameters (14 nm) exhibited superparamagnetism.…”
Section: Reviewmentioning
confidence: 87%
“…[ 90 ] After overfi lling Ni 80 Fe 20 (permalloy) through molecular beam deposition, planarization using ion beam milling to the PS matrix followed by dry etching enabled the formation of permalloy nanodots as shown in Figure 5 l. The authors also described a climate controlled process enhancing the ordering PS-b -PLA features during self-assembly. A considerable difference in the long range order of the BCP was observed between the two studied annealing environments and thus the resulting evaporated patterned permalloy material.…”
Section: Reviewmentioning
confidence: 99%
“…For example, Olayo-Valles et al [66] [67] demonstrated the fabrication of magnetic dots by overfilling a porous PS template with Ni 80 Fe 20 followed by Ar ion milling and etching (figure 9). A sol-gel replication method was also reported using PS-b-PLA BCPs.…”
Section: (A) Ps-b-pi and Ps-b-pbmentioning
confidence: 99%